Sub1 Rice: Engineering Rice for Climate Change - Emerick, Kyle; Ronald, Pamela C (Cold Spring Harbor perspectives in biology, 2019)
By the year 2100, the number of people on Earth is expected to increase by ∼50%, placing increasing demands on food production in a time when a changing climate is predicted to compromise crop yields. Feeding this future world requires scientifically informed innovations in agriculture. Here, we describe how a rice gene conferring tolerance to prolonged submergence has helped farmers in South and Southeast Asia mitigate rice crop failure during floods. We discuss how planting of this new variety benefited socially disadvantaged groups. This example indicates that investment in agricultural improvement can protect farmers from risks associated with a changing climate.